ANALISIS TAKTIK PERTAHANAN DALAM CABANG OLAHRAGA SEPAKBOLA (STUDI KASUS PADA LIGA INGGRIS, SPANYOL, JERMAN, DAN ITALIA PADA TAHUN 2015-2016) - Irawan, Iswahyudi; Widodo, Achmad (Jurnal Kesehatan Olahraga, 2019)
Football is a very complex sport. To support the goals of football is required of the players in it. That skill can be the benchmark of a defender or an attacker to be able to state the success and failure of a team. The formulation of the problem in this research is how the defense tactics applied by teams with the best defense in each league are English, Spanish, German and Italian leagues in 2015-2016. The purpose of this study is to obtain information about how defense tactics are performed by the best defense teams in Europe 2015-2016. The type of research in this study using qualitative methods of analyzing the theoretical basis in accordance with the facts in the field. It is undeniable that defense tactics are very important in the game of football, because with a solid defense will make the other players can be confident in the game. In a match that runs the team with the best defense in Europe applying defense tactics well, only a few mistakes are made, so the lack of goals. The conclusions from the discussion are Tottenham Hotspurs (England), Atletico Madrid (Spain), Bayern Munchen (Germany) and Juventus (Italy) can play optimally and effectively, and the teams have different defense tactics in apply it. Keywords: football, defense tactic, and effectiveness.